2009
DOI: 10.1051/0004-6361/200811337
|View full text |Cite
|
Sign up to set email alerts
|

Star formation around RCW 120, the perfect bubble

Abstract: Context. This study deals with the star formation triggered by H ii regions.Aims. We wish to take advantage of the very simple morphology of RCW 120 -a perfect bubble -to understand the mechanisms triggering star formation around an H ii region and to establish what kind of stars are formed there.Methods. We present 870 μm observations of RCW 120, obtained with the APEX-LABOCA camera. These show the distribution of cold dust, and thus of neutral material. We use Spitzer-MIPS observations at 24 μm and 70 μm to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
212
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(237 citation statements)
references
References 33 publications
(41 reference statements)
21
212
0
3
Order By: Relevance
“…Moreover, not all massive dust condensations appear as infrared dark clouds. For example, the two most massive condensations (with masses of 200 and 800 M at a distance of 1.3 kpc) observed at 870 μm in the photo-dissociation region (PDR) bordering the RCW 120 H ii region (Deharveng et al 2009) are not detected as IRDCs at 8 or 24 μm. They are hidden, at these wavelengths, by the bright emission of the adjacent foreground PDR.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Moreover, not all massive dust condensations appear as infrared dark clouds. For example, the two most massive condensations (with masses of 200 and 800 M at a distance of 1.3 kpc) observed at 870 μm in the photo-dissociation region (PDR) bordering the RCW 120 H ii region (Deharveng et al 2009) are not detected as IRDCs at 8 or 24 μm. They are hidden, at these wavelengths, by the bright emission of the adjacent foreground PDR.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Observations in mm and sub-mm wavelengths (Zavagno et al 2007;Deharveng et al 2009) show a fragmented neutral layer along its PDR, which contains five of the nine mmcondensations found by Zavagno et al (2007). According to Deharveng et al (2009) the mass of the layer is ∼2000 M .…”
Section: Introductionmentioning
confidence: 93%
“…In the infrared, Churchwell et al (2006) and Churchwell et al (2007) found many 0.1 -10 pc size shells in the GLIMPSE survey covering only a part of the plane of the Milky Way. Deharveng et al (2003), Zavagno et al (2006), Sidorin (2008), and Deharveng et al (2009) identified shells observationally in optical, infrared, radio and other wavebands, some of them appear to have triggered star formation at their borders. Watson et al (2009) analyzed some of the shells from the GLIMPSE survey to determine properties of YSOs related to them.…”
Section: Outside Of a Star Clustermentioning
confidence: 98%